Association between polymorphisms in the adiponectin gene and cardiovascular disease: a meta-analysis - Zhang Huan; Mo Xingbo; Hao Yongchen; Gu Dongfeng (BMC, 2012)
Abstract Background Previous studies have examined the associations between polymorphisms of adiponectin gene (ADIPOQ) and cardiovascular disease (CVD), but those studies have been inconclusive. The aim of this study was to access the relationship between three single nucleotide polymorphisms (SNPs), +45 T > G (rs2241766), +276 G > T (rs1501299) and -11377 C > G (rs266729) in ADIPOQ and CVD. Methods A comprehensive search was conducted to identify all studies on the association of ADIPOQ gene polymorphisms with CVD risk. The fixed and random effect pooled measures (i.e. odds ratio (OR) and 95% confidence interval (CI)) were calculated in the meta-analysis. Heterogeneity among studies was evaluated using Q test and the I2. Publication bias was estimated using modified Egger's linear regression test. Results Thirty-seven studies concerning the associations between the three polymorphisms of ADIPOQ gene and CVD risk were enrolled in this meta-analysis, including 6,398 cases and 10,829 controls for rs2241766, 8,392 cases and 18,730 controls for rs1501299 and 7,835 cases and 14,023 controls for rs266729. The three SNPs were significantly associated with CVD, yielding pooled ORs of 1.22 (95%CI: 1.07, 1.39; P = 0.004), 0.90 (95%CI: 0.83, 0.97; P = 0.007) and 1.09(95%CI: 1.01, 1.17; P = 0.032) for rs2241766, rs1501299 and rs266729, respectively. Rs2241766 and rs1501299 were significantly associated with coronary heart disease (CHD), yielding pooled ORs of 1.29 (95%CI: 1.09, 1.52; P = 0.004) and 0.89 (95%CI: 0.81, 0.99; P = 0.025), respectively. The pooled OR for rs266729 and CHD was 1.09 (95%CI: 0.99, 1.19; P = 0.090). Significant between-study heterogeneity was found in our meta-analysis. Evidence of publication bias was observed in the meta-analysis. Conclusions The present meta-analysis showed that the associations between rs2241766, rs1501299 and rs266729 in the ADIPOQ and CVD were significant but weak. High quality studies are still needed to confirm the associations, especially for rs2241766.